House of cards. The complete first season [videorecording (DVD)] - Willimon, Beau (Sony Pictures Home Entertainment, 2013)
Season one of the Netflix original series House of Cards. Frank Underwood is a cunning career politician. Zoe Barnes is an ambitious young journalist. Together they forge a partnership that trades powerful secrets for political access, and so much more.